2020
DOI: 10.1057/s41287-020-00257-0
|View full text |Cite
|
Sign up to set email alerts
|

Participation in and Gains from Traditional Vegetable Value Chains: a Gendered Analysis of Perceptions of Labour, Income and Expenditure in Producers’ and Traders’ Households

Abstract: Horticulture is one of the fastest growing subsectors of agriculture in Tanzania. Gender relations in vegetable-producing and vegetable-trading households need to be understood to make value chain development equitable. This study, carried out in northern and central Tanzania, is based on data from surveys, focus group discussions and semi-structured interviews. The perceptions of men and women traders and producers are investigated with regard to labour participation in traditional vegetable value chains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Differences in levels of household income between men and women in MHHs can be explained by the fact that male and female respondents belong to different households. However, it must be taken into account that information on income is often not shared between spouses in the study context, with men tending to indicate higher incomes (Fischer et al, 2020). Differences between machine users and non-machine users will be presented in the section History and context of mechanized maize shelling.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in levels of household income between men and women in MHHs can be explained by the fact that male and female respondents belong to different households. However, it must be taken into account that information on income is often not shared between spouses in the study context, with men tending to indicate higher incomes (Fischer et al, 2020). Differences between machine users and non-machine users will be presented in the section History and context of mechanized maize shelling.…”
Section: Methodsmentioning
confidence: 99%
“…In Tanzania, the Traditional African vegetables are mainly produced for subsistence and few for cash. The study carried out in northern and central part of Tanzania to investigate participation of farmers and traders in relation to gender in vegetable production and trading, found farmers reporting more balanced intra-household labour arrangements paired with less-balanced income and expenditure shares, while traders indicated less-balanced labour contributions which went hand in hand with more balanced shares of benefits [51]. The participation of farmers and traders in vegetables shows opportunities to farmers who benefit from trade by selling surplus produce and purchasing needed goods and services [52].…”
Section: Farmers and Tradersmentioning
confidence: 99%
“…Schreinemachers et al (2018) noted that vegetable production forms an integral part of farm diversification and offers an economic opportunity for reducing unemployment and poverty in less developed countries. Fischer et al (2020) also found that traditional vegetable value chains contribute substantially to food and income requirements of women and poor farmers in less privileged areas of sub-Saharan Africa. In Kenya, indigenous vegetables such as chili pepper (Capsicum species) and spider plants (Cleome gynandra) are widely grown by smallholder farmers due to their nutritional and economic importance.…”
Section: Introductionmentioning
confidence: 95%